Analysis of the United States’ Foreign Policy Towards Denuclearization of North Korea’s Nuclear 2017-2021 - Putri, Risalanisa Dwi (Jurnal Diplomasi Pertahanan, 2021)
Since few decades ago, the United States has faced a real threat from one of Soviet Union allies, North Korea. North Korea has built a nuclear facility and the government keeps develop it day by day. To solve the problem, the United States under Trump administration suggested an approach called Maximum Pressure. However, Maximum Pressure could not contain the power and threat that came from North Korea nuclear. The fact is, North Korea still develops it until now and abandons all of the sanctions given by the United States and its allies.